Human hair follicle-derived mesenchymal stem cells improve ovarian function in cyclophosphamide-induced POF mice - Jinhua Mo; Hong Hu; Pengdong Li; Yang Ye; Wanle Chen; Lei Chen; Jing Qiao; Xiaoying Zhao; Qiuxia Yan; Cairong Chen (Stem Cell Research & Therapy)
Abstract Introduction Mesenchymal stem cell (MSCs) of different tissue origins have become a new option for the treatment of premature ovarian failure (POF) as they can recovery the ovarian function. However, there were rarely researches about human hair follicle-derived mesenchymal stem cells (HF-MSCs) in POF. Objectives In this study, we compared the effects of HF-MSCs and human umbilical cord mesenchymal stem cells (HU-MSCs) on POF models to explore the underlying molecular mechanisms. Methods Female mice received intraperitoneal cyclophosphamid for 10 days to induce the POF mice model. One week after drug withdrawal, the mice were randomly divided into four groups according to the tail vein injection of drugs, which were: Control group (CON), Premature ovarian failure group (POF), HF-MSCs treatment group (P–H group) and HU-MSCs treatment group (P–U group). Which Treatment once a week for 4 consecutive times. Serum and ovarian tissues were collected 2 weeks after the last treatment, and fertility was performed by mating. ELISA, HE staining, transmission electron microscopy (TEM) were applied to evaluate the ovarian function, oocytes quantity and quality, and the mechanism was verified by qRT-PCR and western blot. In addition, the tumorigenic risk of organs was assessed by long-term observation. Results The POF mice model was successfully established by intraperitoneal injection of cyclophosphamide 100 mg/kg/d for 10 days. Compared with POF group, two weeks after transplantation, serum FSH decreased, AMH and E2 increased in the P–H and P–U groups of mice (p < 0.05), but there was no significant difference between the P–H and P–U groups (p > 0.05). In addition, the number of primary follicles, secondary follicles and antral follicles in both P–H and P–U groups were significantly increased (p < 0.05), while the atretic follicles was significantly decreased (p < 0.05). The pups in POF group was significantly lower than that in P–H group and P–U group (p < 0. 01). Furthermore, those effects was more significant in P–H group than in P–U group (p < 0.05). In addition, the mitochondrial ultramicrostructure of the ovaries in the four groups showed a significant difference in the mitochondrial morphologies and number. In the POF group, the mitochondria presented a spheroids structure with fewer numbers, serious vacuolation and a disordered mitochondrial cristae arrangement. Nevertheless, after MSCs transplantation into the P–H and P–U group, we could observe ameliorative mitochondrial cristae alignment and vacuolation, as well as a small number of long rod-like structures. Mechanism study showed that KEAP1 protein expression was decreased in the P–H group, which increased the nuclear translocation of NRF2 and upregulated the expression of downstream HO-1 protein. At last, the possibility of tumor development after transplantation of HF-MSCs was excluded by long-term observation and organ anatomical examination. Conclusion HF-MSCs can improve ovarian function in cyclophosphamide-induced POF mice, and the effects were superior to HU-MSCs. The underlying mechanism may by inhibiting ferroptosis of granulosa cells through KEAP1/NRF2/HO-1 pathway.